BERBANTUAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN DAN METODE TUTOR SEBAYA (PEER TUTORING) UNTUK MENINGKATKAN PRESTASI BELAJAR KOMPOSISI FOTO DAN VIDEO (TYPE OF SHOT) - Abdul Rokhim (SPIRIT, 2021)
Abstract: The purpose of this study was to improve the Learning Achievement of Photo and Video Composition (Type of Shot) students of class XI Production and Broadcast Television Program (PSPT) SMK Negeri 1 Bangil, peer tutoring learning methods and assisted by YouTube as a learning medium with 32 students as thesubject. .This research is a classroom action research conducted in two cycles with the stages (1) initial design, (2) observation, (3) reflection, and (4) revised design. Based on the research that has been done, it can be concluded that there is an increase in learning achievement of the Composition of Photos and Videos (Type of Shot) with peer tutoring and assisted by YouTube as a learning medium, namely in cycle I with an average of 68.91 and students. 22 students (68.76%) experienced mastery learning with a value> 70. Whereas in cycle II with an average of 82.97 and students who complete learning as many as 28 students (87.50%), thus the peer tutoring method and assisted by YouTube as a learning medium can improve the learning achievement of Photo and Video Composition ( Type of Shot) students of class XI Production and Broadcast Television Program (PSPT) SMK Negeri 1 Bangil and can be used in other schools on different subjects. Keywords: Youtube, Peer Tutoring, Photo and Video Composition ( Type of Shot)